1991
DOI: 10.1111/j.1440-1630.1991.tb01709.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Relaxation Techniques in Controlling Chemotherapy Induced Nausea: A Literature Review

Abstract: This study was conducted to assist occupational therapists make an informed decision on the possible use of relaxation therapy in helping cancer patients cope with chemotherapy induced nausea. The aim was to review studies that have attempted to demonstrate the effectiveness of relaxation techniques in reducing the conditioned component of this type of nausea. The techniques under review included progressive muscle relaxation as a separate technique, as well as in combination with guided imagery and biofeedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…These three issues are important areas for clients with cancer, and can easily be overlooked. For instance, there is a lack of attention paid to the difficulties with fatigue and weakness in people with cancer (Nail & Winningham, 1995), while relaxation techniques may be used effectively to assist in controlling nausea induced by chemotherapy (Mastenbroek & McGovern, 1991). Occupational therapists can meet these needs by working with the clients individually and in groups to make it easier to cope with the illness and treatment by temporarily modifying their lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…These three issues are important areas for clients with cancer, and can easily be overlooked. For instance, there is a lack of attention paid to the difficulties with fatigue and weakness in people with cancer (Nail & Winningham, 1995), while relaxation techniques may be used effectively to assist in controlling nausea induced by chemotherapy (Mastenbroek & McGovern, 1991). Occupational therapists can meet these needs by working with the clients individually and in groups to make it easier to cope with the illness and treatment by temporarily modifying their lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…An older review of usefulness of relaxation techniques in acute pain management showed however poor performance of these methods [ 102 ]. Relaxation techniques proved to be useful in treatments of nausea of different origins, chemotherapy-caused [ 103 , 104 ] or pregnancy-related [ 105 ]. Beneficiary effects have been reported in Chronic Obstructive Pulmonary Disease (COPD) (regarding both respiratory functions improvement and better psychological wellbeing) [ 106 ] and in ischaemic heart disease recovery efforts [ 107 ].…”
Section: Relaxation Techniquesmentioning
confidence: 99%